Awareness on Geriatric Care and the Quality of Life among Elderly - Queddeng, Mercita Q. (JPAIR Multidisciplinary Research, 2010)
The study determined the awareness on geriatric care and the quality of life among elderly in the selected municipalities in the first district of Ilocos Sur during the calendar year 2009. The respondents of this study were the 355 elderly assisted by their significant others or family members taking care of them from the selected municipalities in the first district of Ilocos Sur namely Magsingal, Sto. Domingo and San Ildefonso. The descriptive method of research was utilized. The data were gathered through the use of questionnaire coupled with interview schedule. The data gathered were analyzed using the frequency count, percentage, mean and simple correlation analysis. The results revealed that most of the respondents are mature adults, mostly female, widowed, reached elementary level; most of them have no job but those who are still earning have a monthly income of Php 1,000.00 and below. Most of the respondents suffer from diseases such as diabetes mellitus, alzheimers and hypertension. They are generally supported with their family members and they are living with them. They are moderately aware on geriatric care along with its dimensions namely: medication and supervision, physical care, and home safety. There is a "high" level of quality of life along with physical, psychological and economic factors. There exist significant relationships between the level of awareness on geriatric care along with age, educational attainment, occupation and pension of the respondents.
Keywords: geriatric care; quality of life; elderly